DAYA PARASITASI Tetrastichus sp. (Hymenoptera : Eulophidae) PADA PUPA Phragmatoecia castaneae (Lepidoptera : Cossidae) DI LABORATORIUM - Dewi L Sidauruk; Maryani Cyccu Tobing; Mena Uly Tarigan (Universitas Sumatera Utara, 2013)
The sugarcane stem borer Phragmatoecia castaneae (Lepidoptera : Cossidae) is a key pest on sugarcane crop in North and West Sumatera. The objective of this research was to study the ability of parasitoid Tetrastichus sp. (Hymenoptera : Eulophidae) on pupa Ph. castaneae H. (Lepidoptera : Cossidae) in the laboratory. This research was carried out at Central Research and Development of Sugarcane Crop Sei Semayang PTPN II Medan from May to July 2012. The method of this research used Randomized Complete Design factorial with 2 factors, the first factor is number of parasitoid (0, 4, 5, 6, and 7 pairs) and the second factor is number of Ph. castaneae (1, 3, 5, 7, and 9 pupa) with three replications. The results showed that the highest percentage parasitisation (100%) on pupa Ph. castaneae was found in treatment 1 pupa with 5, 6, 7 pairs Tetrastichus sp. and the lowest percentage (18,50%) on 9 pupa with 4 pairs Tetrastichus sp. This parasitoid need 10-15 seconds into do copulation. Females of Tetrastichus sp. need 20-25 minutes to put egg into its host. The fastest symptoms in the treatment 1 pupa on 3,47 days and 7 pairs Tetrastichus sp. on 4,73 days, and the lowest in the treatment 9 pupa is 4,47 days. The sex ratio of male and female was 1:3,3. Key words : Phragmatoecia castaneae, Tetrastichus sp, ability of parasitoid.